Methodology for increasing the level of understanding of a literary text by university students based on the author-reader relationship model (Journal of Educational Sciences, 2024)
The article considers the problem of increasing the level of understanding of students' works of art within the framework of the relationship between the author and the reader. Two different approaches to the reception of artistic texts are highlighted, and, based on our research, we consider the text as a platform for the reader to express their attitude towards the artistic reality presented by the author in the work. From the point of view of the triad “Author-text-reader”, three different aspects of deep consideration of the meaning of the text are described. Each of them will be considered separately, and the opinion of the students will be clarified. A work of art is considered as an event based on the relationship between the author and the reader. Accordingly, the need to create modern effective methods of understanding the work of art based on the relationship between the author and the reader is determined. By differentiating innovative searches on this question, objects are grouped that determine the relationship between the author and the reader. As a result, a new model of author-reader relations will be developed. The effectiveness of the theoretical concept is tested in practice. According to the results of the defining stage, it turns out that students, when analyzing a work of art, limit their attention only to the plot, the content of the story, and try to find manifestations of the author's position. On the basis of the current results, a “reading diary” is offered, the purpose of which is the conscious reading of a work of art by a student. It is concluded that the proposed approach helps to increase the level of understanding of the artistic text. 30 students of Suleiman Demirel University took part in the testing of the methodology.Keywords: author; triad “author-text-reader”; fiction; author-reader relationship; methods of teaching literature; “reading diary”.